DNA Damage: From Chronic Inflammation to Age-Related Deterioration - Ioannidou, Anna; Goulielmaki, Evi; Garinis, George A. (Frontiers in Genetics, 2016)
To lessen the “wear and tear” of existence, cells have evolved mechanisms that continuously sense DNA lesions, repair DNA damage and restore the compromised genome back to its native form. Besides genome maintenance pathways, multi-cellular organisms may also employ adaptive and innate immune mechanisms to guard themselves against bacteria or viruses. Recent evidence points to reciprocal interactions between DNA repair, DNA damage responses and aspects of immunity; both self-maintenance and defense responses share a battery of common players and signaling pathways aimed at safeguarding our bodily functions over time. In the short-term, this functional interplay would allow injured cells to restore damaged DNA templates or communicate their compromised state to the micro-environment. In the long-term, however, it may result in the (premature) onset of age-related degeneration, including cancer. Here, we discuss the beneficial and unrewarding outcomes of DNA damage-driven inflammation in the context of tissue-specific pathology and disease progression.